Approximate Bayesian computation for a spatial susceptible-exposed-infectious-removed model - Fabris-Rotelli, Inger Nicolette (University of Pretoria, 2022)
Mini Dissertation (MSc (Advanced Data Analytics))--University of Pretoria, 2021.